Infection and Sepsis Trends during United States' Delivery Hospitalizations from 2000 to 2020 - Liu, Lilly Y.; Friedman, Alexander M.; Goffman, Dena; Nathan, Lisa; Sheen, Jean-Ju; Reddy, Uma M.; D'Alton, Mary E.; Wen, Timothy (American Journal of Perinatology, 2024)
Objective This study aimed to evaluate trends, risk factors, and outcomes associated with infections and sepsis during delivery hospitalizations in the United States.Study Design The 2000–2020 National Inpatient Sample was used for this repeated cross-sectional analysis. Delivery hospitalizations of patients aged 15 to 54 with and without infection and sepsis were identified. Common infection diagnoses during delivery hospitalizations analyzed included (i) pyelonephritis, (ii) pneumonia/influenza, (iii) endometritis, (iv) cholecystitis, (v) chorioamnionitis, and (vi) wound infection. Temporal trends in sepsis and infection during delivery hospitalizations were analyzed. The associations between sepsis and infection and common chronic health conditions including asthma, chronic hypertension, pregestational diabetes, and obesity were analyzed. The associations between clinical, demographic, and hospital characteristics, and infection and sepsis were determined with unadjusted and adjusted logistic regression models with unadjusted odds ratio (OR) and adjusted odds ratios with 95% confidence intervals as measures of association.Results An estimated 80,158,622 delivery hospitalizations were identified and included in the analysis, of which 2,766,947 (3.5%) had an infection diagnosis and 32,614 had a sepsis diagnosis (4.1 per 10,000). The most common infection diagnosis was chorioamnionitis (2.7% of deliveries) followed by endometritis (0.4%), and wound infections (0.3%). Infection and sepsis were more common in the setting of chronic health conditions. Evaluating trends in individual infection diagnoses, endometritis and wound infection decreased over the study period both for patients with and without chronic conditions, while risk for pyelonephritis and pneumonia/influenza increased. Sepsis increased over the study period for deliveries with and without chronic condition diagnoses. Risks for adverse outcomes including mortality, severe maternal morbidity, the critical care composite, and acute renal failure were all significantly increased in the presence of sepsis and infection.Conclusion Endometritis and wound infections decreased over the study period while risk for sepsis increased. Infection and sepsis were associated with chronic health conditions and accounted for a significant proportion of adverse obstetric outcomes including severe maternal morbidity.Key Points
Keywords: obstetric sepsis; maternal safety; maternal outcomes; severe maternal morbidity